(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2026)
Background: The problem of toxic leadership became a major organizational problem in the hospitality industry, and its negative impact on the welfare of the personnel, the quality of the provided service, as well as the sustainability of the organization. Objective: The aim of the research was to study the antecedents, consequences, and corrective factors related to toxic leadership within the hotel sector, in the context of the Delhi-NCR area. Methodology: The quantitative research design was used with cross-sectional design, and the data were gathered among 400 employees in 30 hotels (3-star to 5-star group). Toxic leadership, emotional exhaustion, turnover intention, perceived service quality, and the servant leadership were measured using structured questionnaires with validated scales. Results: The results showed that the most common toxic leadership traits that were perceived by the hotel employees were narcissism, self-promotion, and authoritarianism. Servant leadership was shown to be a major preventive element, and it minimized burnout and increased job satisfaction and retention intentions. The findings indicated that organizational culture and ineffective accountability systems promoted the presence of toxic leadership in hotels. Conclusion: This study added value to the existing bodies of literature since it brought the toxic triangle and Job Demands- Resources models to the hospitality environment. Pragmatic implications included leadership reforms, moral training, and start-up of anonymous feedback to reduce the toxic effects of leadership.